Energy consumption performance using natural ventilation in dwelling design and CFD simulation in a hot dry climate: A case study in Sudan - Jeradat, Amer; Elhassan, Zeinab A. (Frontiers in Built Environment, 2023)
Introduction: Sudan is taking proactive steps towards environmental sustainability, including initiatives to improve energy efficiency and reduce costs in a hot, dry climate. This article assesses the contribution of natural ventilation to heat transfer and temperature conditioning in urban areas in Khartoum, Sudan. Methods: The research methodology used a combination of building modeling with computational fluid dynamics (CFD) integrated with IESV Autodesk software to model natural ventilation and simulate energy consumption by incorporating natural ventilation into home design. Results: The best-case scenario for natural ventilation resulted in a 71.1% yearly energy savings. The design point of internal air speed was approximately 0.7 m/s, the point at which 95% of the indoor areas had an average air speed between 0.43 m/s and 0.9 m/s. The worst-case scenario occurred in the east/west direction, when 80% of the interior had an airflow between 0.05 m/s and 0.01 m/s; near open windows, the airflow was approximately 0.1 m/s. Discussion: This study was the first research in Khartoum on the design of clean and energy-saving sustainable architecture. The architectural design process for energy-efficient living in the urban region of Al-Azhari City was implemented and defined in a city quarter in Khartoum. The results showed that natural ventilation can maintain a comfortable indoor temperature in summer and significantly reduce energy costs. The findings may have implications for the design of sustainable buildings in other hot, dry climates.